Johannes Calvyn oor gebedsverhoring - P. C. Potgieter (Acta Theologica)
Calvin has written extensively on prayer, not only in his Institutes, but also in his commentaries, sermons and letters. His views in this regard have been reflected in a substantial number of publications by various Calvin scholars. This article particularly researches his views on God’s answering of prayer, on which relatively little has been published yet. Some of Calvin’s views in this regard may be debatable — for instance his huge and often repeated emphasis on repentance as primary element of prayer, and his view that in delaying his answer to our prayers God is exercising us in patience. On the other hand he has said much that may currently be of significant importance for theology, and particularly for the pastoral care of the faithful in their search for understanding the ways of God.